Dinamika Keterwakilan Perempuan dalam Proses Pembentukan UU TPKS 2022: Partisipasi dan Implikasinya terhadap Substansi Kebijakan - Salma, Zahra Hanifah; Misbah, Revalyza; Dewi, Tias Rahma; Wulandari, Lia (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2025)
Sexual violence is a form of human rights violation that is complex and continues to increase, especially against women. According to data from SIMFONI PPA and the National Commission on Violence Against Women (Komnas Perempuan), sexual violence cases peaked in 2022, highlighting the urgent need for more progressive legal protection. This study aims to analyze the dynamics of women's representation in the formation process of the 2022 Law on Sexual Violence Crimes (UU TPKS) and examine the implications of their participation on the substance and implementation of the policy. The research employs a descriptive qualitative approach using library research methods. The findings indicate that women, including legislators, activists, academics, and civil society organizations, play a strategic role in initiating, advocating for, and overseeing the discussion of the UU TPKS. Their involvement is not merely symbolic but also significantly influences the substance of the policy, making it more responsive to victims by prioritizing gender justice principles and a victim-centered approach. Additionally, women's participation strengthens the implementation of the law through the monitoring of regulations, training for officials, and ensuring victims' rights to protection, support, and recovery. This study emphasizes that women's representation in the legislative process is not just about numbers but about substantive representation that can determine the quality and direction of policies. Therefore, it is essential to continue encouraging the presence of women in public policy-making processes in Indonesia.